The Total Cost of Transactions on the NYSE - BERKOWITZ, STEPHEN A.; LOGUE, DENNIS E.; NOSER, EUGENE A. (Journal of Finance, 1988)
ABSTRACT This paper develops a measure of execution costs (market impact) of transactions on the NYSE. The measure is the volume‐weighted average price over the trading day. It yields results that are less biased than measures that use single prices, such as closes. The paper then applies this measure to a data set containing more than 14,000 actual trades. We show that total transaction costs, commission plus market impact costs, average twenty‐three basis points of principal value for our sample. Commission costs, averaging eighteen basis points, are considerably higher than execution costs, which average five basis points. They vary slightly across brokers and significantly across money managers. Though brokers do not incur consistently high or low transaction costs, money managers experience persistently high or lost costs. Finally, the paper explores the possible tradeoff between commission expenditures and market impact costs. Paying higher commissions does not yield commensurately lower execution costs, even after adjusting for trade difficulty. We cannot determine whether other valuable brokerage services are being purchased with higher commission payments or whether some money managers really are inefficient consumers of brokerage trading services.